Composition and community structure of bivalve in Buntal Beach - Awg. Mohd. Shahryzan, Awang Omar (Universiti Malaysia Sarawak, (UNIMAS), 2018)
Bivalves are one of the classes that belong to Phylum Mollusca. Bivalves have some very important roles in the ecosystem. The study of bivalve in Buntal beach was carried out in order to provide additional information regarding the bivalve community in Sarawak. Organism samples and sediment samples were taken three times for replicates at six stations. Data collected such as number of individuals and water parameters were analyzed by using Graphpad Prism 7.0, one-way ANOVA and Pearson correlation. Species density were heavily influenced by temperature and chlorophyll a availability.